2018
DOI: 10.14444/5059
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Comparison of Thermal Tissue Effects from Traditional Electrosurgery and a Low-Temperature Electrosurgical Device during Anterior Cervical Discectomy and Fusion

Abstract: Background: Exposure of the anterior cervical spine requires dissection in proximity to critical neurovascular structures. Monopolar electrosurgical (ES) devices generate heat in contacted tissues, resulting in thermal damage and temperature change. This study examined depth of thermal injury and temperature change associated with use of a lowtemperature electrosurgical device (LTD) compared to traditional electrosurgery during a cadaveric anterior cervical discectomy and fusion (ACDF) dissection.Methods: ACDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Vijay et al determined that lower vitamin D level played an important role in a lower rate of and a longer time to fusion. [ 29 , 30 ] In our study, we also found that serum vitamin D (OR = 0.79, P < .001) was significant predictor of nonunion. These findings indicate it is necessary to proceed a prospective study to analyze the role of vitamin D supplementation on spinal fusion.…”
Section: Discussionsupporting
confidence: 74%
“…Vijay et al determined that lower vitamin D level played an important role in a lower rate of and a longer time to fusion. [ 29 , 30 ] In our study, we also found that serum vitamin D (OR = 0.79, P < .001) was significant predictor of nonunion. These findings indicate it is necessary to proceed a prospective study to analyze the role of vitamin D supplementation on spinal fusion.…”
Section: Discussionsupporting
confidence: 74%